Analysis of Factors Affecting Labor Absorption in the Small and Medium Industry Sector in West Nusa Tenggara Province in 2019-2023 - Yudita Septia Andini; Luluk Fadliyanti; Vici Handalusia Husni (West Science Journal Economic and Entrepreneurship, 2025)
This study aims to determine the effect of Investment Value, Production Value and District Minimum Wage on Labor Absorption in the Small and Medium Industry Sector of West Nusa Tenggara Province. The type of research used is quantitative research. The data used is secondary data taken from the West Nusa Tenggara Provincial Industry Service. The data collection technique is documents. The data analysis method uses panel data regression using the eviews 9 analysis tool. The panel data in this study is a combination of cross-section data (data from 10 cities/regencies in West Nusa Tenggara Province) and team series data (data from 2019-2023). The results of the data analysis show that the variables Investment Value, Production Value and Provincial Minimum Wage together (simultaneously) have a significant effect on Labor Absorption in the Small and Medium Industry Sector in West Nusa Tenggara Province. Individually (partially), the Investment Value variable and the District Minimum Wage variable have a positive and significant effect on Labor Absorption, while the Production Value variable has a negative and insignificant effect on Labor Absorption in Small and Medium Industries in West Nusa Tenggara Province.